Microbial Isolation Derived from Pineapple Extract and Its Application on Cocoa Pod Rot Disease, Phytophthora palmivora - Sylvia Sjam; Ade Rosmana; Danial Rahim; Vien Sartika Dewi; Untung Surapati (Indonesian Coffee and Cocoa Research Institute, 2014)
Cocoa pod rot, caused by Phytophthora palmivora,is one of the most important diseases in cocoa farm of Indonesia. Yield losses due to the disease were estimated in the range of 33–99%. Pod rot disease could be controlled using antagonistic fungi, Trichodermasp. and Gliocladiumsp., isolated from pineapple extract. The objective of this study was to evaluate the effectiveness of the two microbes derived from pineapple extract in suppressing the cocoa pod rot disease. The research was conducted at the Plant Pathology Laboratory, Faculty of Agriculture, Hasanuddin University and Cocoa Plantation of Pattalassang II Farmers Group, Pattalassang Village, District of Bantaeng, South Sulawesi from May to September 2012. The results indicated that two species of antagonistic fungi, Trichodermasp. and Gliocladiumsp. were dominant in pineapples extract. The mixture of both of microbes showed the ability to suppress the development of pod rot disease on cocoa plantation. Key worlds: cocoa pod rod, Phytophthora palmivora, Trichoderma sp., Gliocladium sp.